Inactive fatty acids are unable to flip-flop across the lipid bilayer - Jezek, P; Modrianský, M; Garlid, K D (FEBS letters, 1997)
Free fatty acids (FA) were found which did not acidify liposome interior. This is interpreted as their inability to rapidly flip-flop across the lipid bilayer. However, they were able to partition in lipids as detected directly using HPLC or from the shift of their equilibrium binding to acrylodated intestinal binding protein (ADIFAB) in the presence of vesicles. Various bipolar FA, such as 12-hydroxylauric acid, dicarboxylic acids, or FA with benzene ring at the tail were found to be inactive in this way. A phenomenon of shielding, where an additional alkyl chain or non-polar group can restore the flip-flop activity, is described.
Keywords: Carrier Proteins; fluorescenční barviva; Liposomes; vysokoúčinná kapalinová chromatografie; Recombinant Proteins; ionofory; kinetika; Lipid Bilayers; vazba proteinů; chinolinové sloučeniny; Hydrogen-Ion Concentration; Fatty Acids; transportní proteiny; koncentrace vodíkových iontů; rekombinantní proteiny; Protons; Ionophores; Quinolinium Compounds; Fluorescent Dyes; Protein Binding; liposomy; proteiny vázající mastné kyseliny; Fatty Acid-Binding Proteins; Kinetics; valinomycin; mastné kyseliny; Chromatography, High Pressure Liquid; lipidové dvojvrstvy; Valinomycin; protony